Determinan Pertumbuhan Ekonomi Indonesia - Tri Wahyuni Meilinda; Rona Aldies Haribunda Putri; Vennesa Bagus Oktaviani; Wahyu Ria Devissta; Jihad Lukis Panjawa (Universitas 45 Surabaya, 2024)
Indonesia can achieve stable economic growth. Achieving this requires continuous efforts in designing economic policies that are inclusive and oriented towards community empowerment. Therefore, this study aims to assess the impact of investment, inflation, unemployment, and exports on Indonesia's economic growth interpreted by Gross Domestic Product (GDP) from 1991 - 2022. The Autoregressive Distributed Lag - Error Correction Model (ARDL-ECM) method is used in analyzing time series data to analyze the effect of investment, inflation, unemployment, and export variables on GDP in the long and short term. The findings show that investment and unemployment do not have a significant impact on economic growth, in the long or short term. On the other hand, the probability values of inflation and exports have a significant impact on economic growth, both in the long and short term. Analysis of factors that have an impact on increasing economic growth is important as a reference for local governments in increasing economic growth.